Cultivating collective teacher innovativeness in high power distance settings: The role of empowering leadership and collective teacher efficacy - Kavgaci, Hasan; Savas, Gokhan; Ozdemir, Nedim; Kilinc, Ali Cagatay (Pergamon-Elsevier Science Ltd, 2026)
This study examines a moderated mediation model that links empowering leadership to collective teacher innovativeness, with collective teacher efficacy serving as the mediator and school power distance as the moderator. Drawing on a cross-sectional survey design and utilizing data from 926 teachers across 73 schools in T & uuml;rkiye, we employed multilevel structural equation modelling with Bayesian estimation to examine the structural interrelations among the study constructs. The results reaffirmed the mediated effects model, showing that empowering leadership exerts a significant indirect effect on collective teacher innovativeness through collective teacher efficacy. Further analyses demonstrated that school power distance functions as a key contextual variable, amplifying the conditional indirect effect of empowering leadership on collective teacher innovativeness. We conclude with implications for policy and practice.
Keywords: Collective Teacher Innovativeness; Empowering Leadership; Collective Teacher Efficacy; School Power Distance; Multilevel Moderated Mediation